Oxidative mechanism of chicken wooden breast myofibrillar protein - Ke Wang; Yimin Zhang; Jingxin Sun (Food Science and Human Wellness)
To explore the oxidation mechanism of wooden breast myofibrillar protein (WBMP), oxidative breast MP (OBMP) was obtained from different doses (3, 10, and 20 mmol/L) of H2O2 oxidized normal breast MP (NBMP). The results showed that the Zeta-potential, particle size, solubility, sulfhydryl, and carbonyl contents of OBMP-3 (3 mmol/L, low-dose free radicals) and WBMP were similar. Fluorescence spectrum analysis showed that the oxidation of low-dose free radicals led to a significant increase in the surface hydrophobicity (from 214.03 ± 10.03 to 393.50 ± 10.33) and tryptophan fluorescence intensity (from 185.71 to 568.32). In addition, the α-helix content of WBMP decreased significantly from (37.46 ± 1.15)% (NBMP) to (34.70 ± 2.04)%, while β-sheet and random coil contents increased significantly (P < 0.05) from (14.37 ± 0.69)% and (22.24 ± 0.78)% (NBMP) to (17.70 ± 0.87)% and (25.20 ± 1.47)% (WBMP). In summary, low-dose free radical oxidation attacks protein groups, inducing secondary and tertiary structural changes, leading to the formation of WBMP. This work will provide a theoretical basis at the molecular level for exploring the mechanism of functional degradation of WBMP.